Understanding the Role of Repeat Victims in the Production of Annual US Victimization Rates - Planty, Michael (Journal of quantitative criminology, 2007)
Victimization incidence rates produced from the National Crime Victimization Survey (NCVS) are a generally accepted annual indicator of the amount and type of crime in the United States. However, persons who report a large number of similar victimizations—known as series victimizations in the NCVS—are currently excluded in government reports of annual violent victimizations. This paper quantifies the effect of series incident counting procedures on national estimates of violent victimization. The findings suggest that these high-volume repeat victims can have a significant impact on the magnitude and distribution of violent victimization. Current government counting rules that exclude series incidents do not include about three out of every five violent victimizations and distorts the characterization and risk of violence in the United States. However, the inclusion of series incidents introduces significant estimate instability. One remedy is to use prevalence rates in concert with incidence rates to present a more complete and reliable picture of victimization.